PEMANFAATAN MEDIA SOSIAL DALAM KEGIATAN BELAJAR MENGAJAR PADA MASA COVID-19 DI MI AL-IMAN WAY JEPARA - Dewi Tri Santi (As-Salam: Jurnal Studi Hukum Islam & Pendidikan, 2020)
This article aims to examine the use of social media at MI Al-Iman Way Jepara during the Covid-19 pandemic. The data from this study were obtained from observation, interviews, and documentation. The results of this study indicate that social media provides benefits to students, parents, teachers in online learning activities. Barriers to the use of social media occur because the facilities and infrastructure at educational institutions are not fulfilled. In addition, not all social media can be used by teachers and parents, given their low technological skills. This shows that the use of social media as a medium and learning resource in the midst of this pandemic has not been optimal. The positive contribution of this research to education in Indonesia is to provide information to educational institutions to be able to anticipate the COVID-19 pandemic by utilizing social media as a medium for learning online by paying attention to the level of understanding of its users.